ANALISIS EFEKTIVITAS PENGELOLAAN PIUTANG PADA PT. PLN (PERSERO) RAYON KOTA AMBON - Sherly Rutumalessy (P3M Politeknik Negeri Ambon, 2022)
PT.PLN (Persero) Rayon Kota Ambon is a form of service company that provides electricity services to the public. In reality, there are arrears in electricity payments made by electricity customers such as households, hospitals, and other users which results in a delay in paying electricity bills.This study aims to determine the level of accounts receivable turnover and the average period of collection of receivables at PT. PLN (Persero) Rayon Kota Ambon. The analysis technique used in answering research problems is through 3 (three) stages, including: analyzing the average receivable collection, calculating the receivables turnover rate and the receivables collection period.The results of the research show that the average collection of receivables in 2019 is IDR 209,852,537, while for 2020 it is IDR 510,811,866. The receivables turnover rate from 2019 to 2020 has decreased. In 2019 the receivables turnover rate was 2.4 times turnover, while in 2020 it decreased by 1.3 turnovers or the difference in the decrease was 1.1 turnovers. In addition, the average collection of receivables for 2019 was 150 days, and for 2020 it was 277 days.